2004
DOI: 10.1111/j.0021-8782.2004.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between FGF and Wnt signals and Tbx3 gene expression in mammary gland initiation in mouse embryos

Abstract: Interactions between Wnts, Fgfs and Tbx genes are involved in limb initiation and the same gene families have been implicated in mammary gland development. Here we explore how these genes act together in mammary gland initiation. We compared expression of Tbx3 , the gene associated with the human condition ulnar-mammary syndrome, expression of the gene encoding the dual-specificity MAPK phosphatase Pyst1 /MKP3, which is an early response to FGFR1 signalling (as judged by sensitivity to the SU5402 inhibitor), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 53 publications
6
98
0
Order By: Relevance
“…S1 A-C and Datasets S1 and S2). Up-regulated genes included the mammary epithelium markers Krt8, Bmp2, Fgf17, Gata3, Pthlh, and Tbx3 (30,(43)(44)(45)(46)(47), as well as the mammary mesenchyme-specific genes Tbx18, Esr1, and Meox2 (30), thus validating our experimental approach (Fig. 1B and Datasets S1 and S2).…”
Section: Resultssupporting
confidence: 70%
“…S1 A-C and Datasets S1 and S2). Up-regulated genes included the mammary epithelium markers Krt8, Bmp2, Fgf17, Gata3, Pthlh, and Tbx3 (30,(43)(44)(45)(46)(47), as well as the mammary mesenchyme-specific genes Tbx18, Esr1, and Meox2 (30), thus validating our experimental approach (Fig. 1B and Datasets S1 and S2).…”
Section: Resultssupporting
confidence: 70%
“…This gene plays a critical role in guiding the expression of T-box gene family in embryonic stem cell differentiation [31]. T-box3 , a member of the T-box gene family, has been reported to influence the development of mammary gland placodes via interacting with Wnt family member 10 ( Wnt10 ), lymphoid enhancer binding factor 1 ( lef-1 ), and fibroblast growth factor 10 ( Fgf10 ) [3234]. Moreover, T-box3 variants have been implicated in the Ulnar-Mammary Syndrome in humans, a genetic disease characterized by nipple and breast hypoplasia or aplasia [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that TBX3 regulates this signalling pathway during mammary gland development and it has also been suggested that TBX3 lies downstream of FGF (86). Fillmore et al demonstrated that oestrogen and FGF signalling upregulated the expression of TBX3 in breast cancer (63).…”
Section: Fibroblast Growth Factor (Fgf) Signalling Pathwaymentioning
confidence: 99%